Layanan Dasar Bidang Belajar - Lubis, Shabrina Nailah; Alfianita, Fina; Nurul Febrianti, Khoirun Nisak; Fatma A A, Razana Mujahida; Laili R S, Paramesti Ananda (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2025)
Basic learning guidance services play a crucial role in supporting students’ academic success and holistic development. Individual differences in character, abilities, and learning styles require systematic guidance to help students maximize their potential. This study aims to elaborate on the concepts, objectives, service types, implementation, and challenges of basic learning guidance services in schools. The research applied a literature review method by examining journals, books, and policy documents published within the last decade. The findings indicate that basic services consist of key components such as classroom guidance, orientation, information, group guidance, and data collection. These services are designed to foster positive attitudes, develop effective learning skills, and assist students in overcoming academic difficulties. However, implementation is still hindered by limited counseling teachers, inadequate facilities, and a low level of public awareness of the importance of these services. The study concludes that basic learning guidance services are essential in education and should be strengthened through collaboration among stakeholders, technology integration, and continuous counselor training to more effectively support students’ academic achievement and overall development.